INVESTIGATION THE EFFECTS OF GREEN MORTAR PARAMETERS USING ANALYTICAL METHODS - Dawood, Eethar; Abdullah, Mafaz (Journal of Applied Engineering Science, 2021)
The various green mortar mixes have been used in this study using various percentages of waste glass powder (WGP), steel slag (SG) and Micro-silica fume(SF).The different properties of flow, density, ultrasonic pulse velocity (UPV), compressive and flexural strengths have been tested for such green mortar in the first phase of experimental work. The second phase deals with the regression analysis of such properties. Whereas, the analysis of the results have also been using the integrated AHP and TOPSIS methods for selection the best performance of the green mortar due to the ecological effects of such materials. The results showed that the use of 70%OPC+8%WGP+12%SG+10% SF indicated as the best performance in term of ecological impact compared with other mortar mixes. Also, the regression analysis using the integrated AHP and TOPSIS methods gives an effective strategy for the selection of the best mortar mix.